Analisis K-Nearest Neighbour Dalam Mendiagnosa Grandemultipara - Asyahri Hadi Nasyuha; Muhammad Zunaidi; Purwadi Purwadi (Universitas Budi Darma, 2022)
Grandemultipara are women who give birth more than four times usually experience complications in pregnancy and childbirth. Grandemultipara or better known as mothers who give birth more than 4 times can cause various pregnancy complications that will be experienced by the mother, one of which is bleeding. Grandemultipara pregnancies are included in high-risk pregnancies, because complications can occur either during pregnancy or childbirth. The K-NN algorithm can be applied in the process of diagnosing human diseases, so several references are taken including those used in diagnosing several diseases. With the K-NN algorithm that will be used in this study, where data on symptoms of Grandemultipara disease obtained from an expert is processed according to the algorithm to produce accurate diagnostic information for Grandemultipara disease. Analysis of the K-NN method is able to provide information and solutions in solving the problems of Grandemultipara disease.